STUDI TENTANG PERAN IBU DALAM MEMENUHI KEBUTUHAN GIZI SEIMBANG BATITA DI DUSUN SETOYO DESA BALONGMOJO KECAMATAN PURI KABUPATEN MOJOKERTO - Nur Hidayati, Rina (JURNAL KEPERAWATAN SEHAT, 2015)
Toddlers period (children aged 1-3 years) are a golden period in the growth and development of children. Depending toddler in nutrition is very dependent on the role of parents, especially mother. The purpose of this research determined the role of the mother in the nutritional needing of toddlers in Setoyo village, Mojokerto. Design study used descriptive. Samples were obtained as many as 20 people who had inclusion criteria by taking purposive sampling technique. Data was taken using a questionnaire containing 20 questions. The research result was gotten as many as 11 people with a percentage of 60% a negative role, due to the lack of education factor. The understanding of its role as a determinant of maternal nutrition can be improved toddler nutrition counseling when they attended Posyandu. Mother is also expected to actively search for information about nutritional requirements needed by toddlers through print media, electronic media and ask questions directly to health workers, so that through the understanding of the expected role of the mother in the toddlers nutrition can be improved.Keywords: Toddlers, Nutrition, Role